The end of words - Turrell, Ford (The journal for cultural and religious theory, 2006)
A review of Richard Lischer, The End of Words: The Language of Reconciliation In a Culture of Violence. Wm. B. Eerdmans Publishing, 2005. 165 pp + bib. $18.00 (Cloth). ISBN: 0-8028-2932-5.